(untitled) (Journal of Hama University, 2020)
The aim of the research is to study the availability of the requirements for implementing the strategy of partial internal administrative reform in the Directorate of Education in Lattakia, the Department of Vocational Education. The researcher took the four requirements that were agreed upon by most studies, which are simplifying procedures, evaluating performance in order to develop an organizational structure, providing reward and accountability authority, and developing information systems while spreading a culture Reform: In order to conduct the study, the researcher followed the descriptive approach. A questionnaire was distributed to 98 administrators in the directorate, school principals, heads of technical lessons and heads of departments. SPSS20 was used to analyze data, and a set of results was reached, the most important of which is that there are some requirements but they need to be strengthened, the most important of which The Education Directorate is seeking the vocational education department to simplify the procedures and reduce the centralization, providing a system for evaluating the performance of workers, and accountability and accountability in the event of non-compliance with the application of work regulations. The study also showed many shortcomings in providing most of the requirements of the partial internal reform strategy in the Directorate of Education in Lattakia (Department of Education Professional)) the most important of which is the directorate not using e-management instead of Ed In the traditional processes of administration, and the lack of exchange of information and data at the various administrative levels easily and simply, the researcher recommended a number of recommendations, the most important of which is the immediate pursuit of electronic management in the Directorate of Education in Latakia (Vocational Education Department).